Pattern of resilient age-related measles immunity - A. G. Sonis (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Epidemiological situation describing global measles spread is ambiguous. Along with countries succeeded in measles eradication, there are those wherein measles rate remains at quite high level. Because measles is a vaccine-preventable infection, it may then be eradicated solely by ensuring sufficient population coverage with preventive vaccination. The aim of our study was to assess level of measles immunity in medical workers at the Clinics of Samara State Medical University as well as the Samara State Medical University. There were enrolled 1503 subjects (aged 18–79 years), among which all individuals under 55 (77.58%) but not older counterparts provided with medical record on previous measles vaccination or measles infection. Level of serum measles virus-specific IgG antibodies was measured by using ELISA (VektoKor-IgG, JSC Vector-Best, Novosibirsk), with mean concentration ranging in general population within 1.02±0.02 IU/ ml. Positive results were observed in 72.52% of the examined individuals. Average vs. high measles virus-specific IgG level was detected in 52.90% (mean age — 41.4±0.5 years) and 19.62% (mean age — 54.2±0.72 years) of individuals, whereas at level below threshold — in 27.48% of subjects (mean age — 33.25±0.53 years). Thus, in 34.16% of the surveyed vaccinated individuals mostly presented by young subjects contained anti-measles virus-specific antibodies below protective level. Older age groups were shown to increase in average IgG amount with age. Interestingly, age-related measles immunity pattern was observed: percentage of subjects with high vs. low measles virus-specific IgG level increases and decreases, respectively. Taking into consideration a large percentage of subjects previously vaccinated against measles among carriers of low measles immunity, it may be concluded that measles virus-specific IgG antibody level must be monitored in young adulthood to decide of whether subsequent revaccination is necessary.